Prevalence and risk factors associated with malnutrition among adolescents in rural Tanzania. Issue 1 (20th November 2019) - Ismail, Abbas; Darling, Anne Marie; Mosha, Dominic; Fawzi, Wafaie; Sudfeld, Christopher; Sando, Mary Mwanyika; Abdallah Noor, Ramadhani; Charles, James; Vuai, Said
Abstract: Objective: To determine the prevalence and risk factors associated with malnutrition among adolescents in a rural Tanzanian community. Methods: Cross‐sectional survey of 1226 randomly selected adolescents from the Dodoma Health and Demographic Surveillance System (HDSS) in the Chamwino district in the Dodoma region. Anthropometric measurements for weight and height were collected. Height‐for‐age‐ z ‐scores (HAZs) and body mass index (BMI)‐for‐age‐ z ‐scores (BAZs) were computed. Descriptive estimates were documented in graphs and tables, and weighted linear regression models were used to examine predictors of malnutrition. Results: Stunting prevalence was 18%, and thinness prevalence was 14%. Overweight and obesity affected 5.23% of participants. Girls had higher HAZs (β: 0.46, 95% CI 0.33, 0.59, P  < 0.0001) and BAZs (β: 0.20, 95% CI 0.05, 0.35, P  = 0.0098) than boys. Age was inversely associated with HAZs (β: −0.13, 95% CI −0.17, −0.08, P  < 0.0001) and BAZs (β: −0.05, 95% CI −0.10, −0.004, P  = 0.0327). Wealth score (β: 0.10, 95% CI 0.04, 0.16, P  = 0.0009) and dietary diversity score (β: 0.04, 95% CI 0.01, 0.07, P  = 0.0080) were positively associated with HAZs and BAZs. Out‐of‐school adolescents had higher HAZs (β: −0.49, 95% CI −0.75, −0.23, P  = 0.0003) and BAZs (β: −0.68, 95% CI −0.99, −0.37, P  < 0.0001) than adolescents who attended school. Conclusion: There are substantial variations of HAZs and BAZs across gender, age, education and wealth, with an emerging burden of overweight and obesity among adolescents in this rural population. Interventions are urgently required to curb both ends of the malnutrition spectrum. Abstract : Objectif: Déterminer la prévalence et les facteurs de risque associés à la malnutrition chez les adolescents d'une communauté rurale en Tanzanie. Méthodes: Enquête transversale auprès de 1.226 adolescents choisis au hasard dans le Système de Surveillance Démographique et de Santé (SSDS) de Dodoma dans le district de Chamwino, dans la région de Dodoma. Des mesures anthropométriques du poids et de la taille ont été recueillies. Les scores z de la taille pour l'âge (HAZ) et les scores z d'indice de masse corporelle (IMC) pour l'âge (BAZ) ont été calculés. Des estimations descriptives ont été documentées dans des graphiques et des tableaux, et des modèles de régression linéaire pondérés ont été utilisés pour analyser les prédicteurs de la malnutrition. Résultats: La prévalence du retard de croissance était de 18% et la prévalence de la maigreur était de 14%. Le surpoids et l'obésité touchaient 5, 23% des participants. Les filles avaient des scores HAZ (β: 0, 46, IC95%: 0, 33–0, 59 ; P  < 0, 0001) et des scores BAZ (β: 0, 20 ; IC95%: 0, 05–0, 35 ; P  = 0, 0098) plus élevés que les garçons. L'âge était inversement associé au score HAZ (β: −0, 13, IC95%: −0, 17, −0, 08, P  < 0, 0001) et au score BAZ (β: −0, 05 ; IC95%: −0, 104, −0, 004 ; P  = 0, 0327). Le score de richesse (β: 0, 10 ; IC95%: 0, 04–0, 16; P  = 0, 0009) et le score de diversité alimentaire (β: 0, 04 ; IC95%: 0, 01–0, 07 ; P  = 0, 0080) étaient positivement associés aux scores HAZ et BAZ. Les adolescents non scolarisés présentaient des scores HAZ (β: −0, 49 ; IC95%: −0, 75, −0, 23 ; P = 0, 0003) et des scores BAZ plus élevés (β: −0, 68 ; IC95%: −0, 99 −0, 37 ; P  < 0, 0001) que les adolescents qui fréquentaient l'école. Conclusion: Il existe des variations substantielles dans les scores HAZ et BAZ selon le sexe, l'âge, l'éducation et la richesse, avec une charge émergente de surpoids et d'obésité chez les adolescents dans la population rurale. Des interventions urgentes sont nécessaires pour réduire les deux extrémités du spectre de la malnutrition.